Strategic Management Analysis Using the VRIO Method and Porter’s Five Forces in UMKM TERAS BAPAK - Nova Nayla Rahmadhani; Saheba Alfi Zahra; Galuh Satya Samantha; 吳阡瑀 吳阡瑀; 黃雅妤 黃雅妤; 余宛庭 余宛庭; 李昱蓁 李昱蓁; 張純螢 張純螢; 林奕弦 林奕弦 (Oikonomia : Journal of Management Economics and Accounting, 2026)
Effective strategic management is a crucial requirement for Micro, Small, and Medium Enterprises (MSMEs) operating on provincial transit routes, particularly amid the rapid growth of the coffee shop industry and intensifying competition. This study analyzes the competitive position of Cafe Teras Bapak, located on Jl. Kertosono-Tulungagung, Kediri, using an integrative approach combining the VRIO framework and Porter’s Five Forces model. The study aims to evaluate internal capabilities, map external competitive dynamics, and formulate a sustainable competitive defense strategy. A descriptive qualitative methodology with a single case study design was employed, in which data were collected through quadrilateral source triangulation: in-depth interviews with the owner, field observations, digital sentiment analysis via Google Maps reviews, and comparative desk research on competitors. VRIO analysis results indicate that Cafe Teras Bapak possesses four sources of sustainable competitive advantage: professional espresso machines (proper coffee), authentic Joglo architecture, membership in Kediri’s pioneer coffee community, and organically built customer loyalty. Meanwhile, Porter’s Five Forces analysis identifies the threat of new entrants as the highest external pressure, successfully counterbalanced by low buyer bargaining power stemming from digitally verified customer loyalty. This study concludes that the integration of Joglo cultural identity with coffee technology specialization constitutes a strong and difficult-to-replicate positioning model for transit route businesses.